The optimal width of the central bank standing facilities corridor and banks' day-to-day liquidity management - Ulrich Bindseil; Juliusz Jabłecki (European Central Bank (ECB), 2011)
Containing short-term volatility of the overnight interest rate is normally considered the main objective of central bank standing facilities. This paper develops a simple stochastic model to show how the width of the central bank standing facilities corridor affects banks' day-to-day liquidity management and the volatility of the overnight rate. It is shown that the wider the corridor, the greater the interbank turnover, the leaner the central bank's balance sheet (i.e. the lower the average recourse to standing facilities) and the greater short-term interest rate volatility. The obtained relationships are matched with central bank preferences to obtain an optimal corridor width. The model is tested against euro area and Hungarian daily data encompassing the financial crisis that began in 2007.
Keywords: E4; E5; 330; liquidity management; money market; standing facilities